2016
DOI: 10.5488/cmp.19.13003
|View full text |Cite
|
Sign up to set email alerts
|

Gyroidal nanoporous carbons - Adsorption and separation properties explored using computer simulations

Abstract: Adsorption and separation properties of gyroidal nanoporous carbons (GNCs) -a new class of exotic nanocarbon materials are studied for the first time using hyper parallel tempering Monte Carlo Simulation technique. Porous structure of GNC models is evaluated by the method proposed by Bhattacharya and Gubbins. All the studied structures are strictly microporous. Next, mechanisms of Ar adsorption are described basing on the analysis of adsorption isotherms, enthalpy plots, the values of Henry's constants, α s an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…where P(d eff ) is a probability of the pores having the effective diameter equal to d eff . Besides, the combination of the BG method and Monte Carlo integration 30,35 has been used to determine the accessible volume within the pores (V acc (d min )).…”
Section: Simulation Boxesmentioning
confidence: 99%
“…where P(d eff ) is a probability of the pores having the effective diameter equal to d eff . Besides, the combination of the BG method and Monte Carlo integration 30,35 has been used to determine the accessible volume within the pores (V acc (d min )).…”
Section: Simulation Boxesmentioning
confidence: 99%
“…For TPMS gyroid structures, diffusion properties can be controlled by a proper choice of gyroid size and density [ 132 ]. Furmaniak et al [ 133 ] reported a theoretical study of Ar adsorption. These authors found a filling process depending on the pore diameter.…”
Section: Glc Properties: What Have We Learnt From Topology and Geometrymentioning
confidence: 99%